A proposed ABCD scoring system for better triage of patients with COVID-19: Use of clinical features and radiopathological findings. Issue 6 (November 2020) - Salunke, Abhijeet Ashok; Warikoo, Vikas; Kumar Pathak, Subodh; Nandy, Kunal; Mujawar, Jalil; Mendhe, Harshal; Shah, Anand; Kottakota, Vishwanth; Menon, Vivek; Pandya, Shashank
Abstract: Background and aims: Currently there are limited tools available for triage of patients with COVID -19. We propose a new ABCD scoring system for patients who have been tested positive for COVID-19. Methods: The ABCD score is for patients who have been tested positive for COVID-19 and admitted in a hospital. This score includes age of the patient, blood tests included leukopenia, lymphocytopenia, CRP level, LDH level, D-Dimer, Chest radiograph and CT Scan, Comorbidities and Dyspnea. Results: The triage score had letters from alphabets which included A, B, C, D. The score was developed using these variables which outputs a value from 0 to 1. We had used the code according to traffic signal system; green(mild), yellow moderate) and red(severe). The suggestions for mild (green)category: symptomatic treatment in ward, in moderate (yellow) category: active treatment, semi critical care and oxygen supplementation, in severe (red) category: critical care and intensive care. Conclusions: This study is, to our knowledge, is the first scoring tool that has been prepared by Indian health care processional's and used alphabets A, B, C, D as variables for evaluation of admitted patients with COVID-19. This triage tool will be helpful in better management of patients with COVID-19. This score component includes clinical and radiopathological findings.A multi-centre study is required to validate all available scoring systems. Highlights: ABCD score can be a tool for triage COVID-19 + patients. This score component includes clinical and radiopathological findings. Use of alphabets can be helpful for health care professionals.